Information security governance and management framework model and toolset for CISOs and decision makers - Volchkov, Andrej (CRC Press, Taylor & Francis Group, 2019)
This book presents a framework to model the main activities of information security management and governance. The same model can be used for any security sub-domain such as cybersecurity, data protection, access rights management, business continuity, etc.